2012
DOI: 10.1590/s0102-86502012001100012
|View full text |Cite
|
Sign up to set email alerts
|

Effect of renal denervation procedure on left ventricular hypertrophy of hypertensive rats and its mechanisms

Abstract: PURPOSE:To investigate the effect of renal denervation (RDN) on the blood pressure, left ventricular hypertrophy and myocardial expression of TLR4/NF-κB in spontaneously hypertensive rats (SHR). METHODS: A total of 36 SHR were randomly assigned into control group (D0), RDN group (D) and sham group (S). 12 WKY rats of same age served as controls (WKY group). Rats in the D0 and WKY groups were sacrificed, but rats in the D and S group were sacrificed at one week and six weeks after surgery. The heart was collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…Hypertension in SHR is a heterogeneous, multifactorial disorder. 46,47 In agreement with previous reports, [48][49][50] in this study, we showed that specific renal sympathetic nervous system ablation causes a transitory decrease in BP in SHR. Transient increases in NA levels were observed 7 days post RDN in the left ventricle of the heart and in the adrenal glands, which resulted in an increase, albeit not significant, in urinary NA levels (7 days), before returning to values similar to those in control SHR by the end of the assessment period.…”
Section: Discussionsupporting
confidence: 93%
“…Hypertension in SHR is a heterogeneous, multifactorial disorder. 46,47 In agreement with previous reports, [48][49][50] in this study, we showed that specific renal sympathetic nervous system ablation causes a transitory decrease in BP in SHR. Transient increases in NA levels were observed 7 days post RDN in the left ventricle of the heart and in the adrenal glands, which resulted in an increase, albeit not significant, in urinary NA levels (7 days), before returning to values similar to those in control SHR by the end of the assessment period.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, TLR4 plays a role in paraventricular nucleusmediated autonomic dysfunction in SHR (Dange et al, 2015) and in rats with angiotensin II-induced hypertension (Dange et al, 2014). Less is known about the contribution of TLR4 on hypertensive kidney dysfunction; however, renal denervation can significantly decrease myocardial TLR4 expression in SHR (Jiang et al, 2012), and angiotensin II upregulates TLR4 expression on mesangial cells (Wolf et al, 2006).…”
Section: B Hypertensionmentioning
confidence: 99%
“…Results of previous animal experiments also support the protective role of RD against LV hypertrophy. In a previous study with SHRs, Jiang et al found that RD can significantly delay the progression of left ventricular hypertrophy, possibly not only through the suppression of sympathetic activity and attenuation of pressure load, but also due to the reduction in myocardial inflammation, as reflected by significantly reduced myocardial levels of Toll like receptor 4 (TLR4), nuclear factor kappa B (NF-κB), tumor necrotic factor alpha (TNF-α) and interleukin 6 (IL-6) after RD ( 22 , 31 ). In a subsequent study in hypertensive type 1 diabetic rats, Thaung et al found that bilateral RD reduces cardiac hypertrophic remodeling in these rats without restoring the attenuated cardiac β-AR responsiveness ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…These observations have been confirmed in subsequent clinical studies ( 18 20 ). Interestingly, some animal studies also found similar benefits of RD on cardiac hypertrophy and cardiac remodeling in various animal models ( 21 23 ), Mechanisms aside from attenuation of blood pressure and reduction in the activity of sympathetic nerves have been proposed to account for these changes, including a reduction in myocardial inflammation ( 22 ). However, whether RD has the ability to attenuate cardiac hypertrophy, induced by pressure overload of the LV, remains to be confirmed, and the potential mechanisms by which this may occur are not currently known.…”
Section: Introductionmentioning
confidence: 88%